PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL KOOPERATIF TIPE NHT DENGAN STRATEGI PEMECAHAN MASALAH (PROBLEM SOLVING) SISTEMATIS BAGI PESERTA DIDIK SMP DI KABUPATEN PRINGSEWU - Fendi Susanto; Indah Resti Ayuni (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
Development of learning tools is a series of processes or activities undertaken to produce a learning device based on existing theories . The purpose of this research is to produce learning tool of NHT model with systematic problem solving strategy , product that produced in the form of Learning Implementation Plan (RPP) and Student Working Sheet (Module ) on Building Material of Flat Space Room that meet valid , effective , and practicalfor junior high school students in Pringsewu . This development research adopted the ADDIE model developed by Dick and Carey and quantitative research methods . The ADDIE model has four stages including analysis , design , development , Implementation , and Evaluation .